2013
DOI: 10.1016/j.ophtha.2012.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics for Genes Associated with Age-related Macular Degeneration in the Comparison of AMD Treatments Trials (CATT)

Abstract: Purpose To evaluate the pharmacogenetic relationship between genotypes of single nucleotide polymorphisms (SNPs) known to be associated with age-related macular degeneration (AMD) and response to treatment with ranibizumab (Lucentis) or bevacizumab (Avastin) for neovascular AMD. Design Clinical trial. Participants 834 (73%) of 1149 patients participating in the Comparison of AMD Treatments Trials (CATT) were recruited through 43 CATT clinical centers. Methods Each patient was genotyped for SNPs rs1061170… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
129
1
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 139 publications
(140 citation statements)
references
References 20 publications
6
129
1
4
Order By: Relevance
“…36 Thus far, the larger studies have not found pharmacogenetic associations with responsiveness to treatment. 37,38 There is, however, emerging evidence that responses to anti-VEGF therapy in n-AMD may be influenced by the genetic profile of the individual. 13,15,18 It is possible that other factors such as lifestyle may also affect the responsiveness to treatment and patients should be encouraged to quit smoking even if there is no evidence of reduced effectiveness of anti-VEGF agents in smokers 39,40 given the link between smoking and AMD and the risk to the fellow eye.…”
Section: Response Based On Change In Va In Terms Of Etdrs Lettersmentioning
confidence: 99%
“…36 Thus far, the larger studies have not found pharmacogenetic associations with responsiveness to treatment. 37,38 There is, however, emerging evidence that responses to anti-VEGF therapy in n-AMD may be influenced by the genetic profile of the individual. 13,15,18 It is possible that other factors such as lifestyle may also affect the responsiveness to treatment and patients should be encouraged to quit smoking even if there is no evidence of reduced effectiveness of anti-VEGF agents in smokers 39,40 given the link between smoking and AMD and the risk to the fellow eye.…”
Section: Response Based On Change In Va In Terms Of Etdrs Lettersmentioning
confidence: 99%
“…There have been reports that CFH Y402H, ARMS2 rs10490924, HTRA1 rs11206038, and VEGFA polymorphisms are associated with responsiveness to ranibizumab treatment (Lee et al, 2009;Smailhodzic et al, 2012;Boltz et al, 2012;Chang et al, 2013). However, in the CATT and IVAN trials, which were multicentric randomized trials, the authors reported that there were no statistically significant associations between the genetic variants and anti-VEGF responsiveness (Hagstrom et al, 2013(Hagstrom et al, , 2014Lotery et al, 2013). Therefore, the association of genetic factors with anti-VEGF treatment responsiveness in neovascular AMD remains unclear (Park et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism underlying this heterogeneity in clinical response is unknown. The genetic factors and variations may be effective on the course of the disease (Hagstrom et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The categorization of the identified SNPs into the two above groups, AMD-related and pharmacologically related SNPs, revealed that the more widely studied AMD-related SNPs have yet to provide a substantiated clinical predictive value (Hagstrom et al, 2013). Anti-VEGF-related SNPs have not yet accumulated the same amount of evidence as AMD-related SNPs either to commend or reject them as potentially useful biomarkers.…”
Section: Association Of Vegf Polymorphisms With Disease Riskmentioning
confidence: 99%